Yttrium oxide film for protecting quartz glass surface from etching by long-term exposure to chlorine trifluoride gas at room temperature. (15th August 2018) - Kawasaki, Ryohei; Umetsu, Yasuhiro; Kurashima, Keisuke; Shioda, Kohei; Hirooka, Asumi; Habuka, Hitoshi
Abstract: The anticorrosive property of yttrium oxide was evaluated using chlorine trifluoride gas. After the exposure to chlorine trifluoride gas at room temperature for the total time longer than 1000 min, the yttrium oxide film, formed on a quartz glass surface, did not show any etching behavior and surface morphology change, while the non-coated quartz glass showed a rough surface with the etching depth of nearly 0.1 mm. Because yttrium oxide had no chemical reaction with chlorine trifluoride gas at temperatures less than 300 °C, yttrium oxide film is expected to protect the quartz glass from etching by chlorine trifluoride gas at room temperature for a significantly long time.